2013
DOI: 10.4314/ijbcs.v7i3.46
|View full text |Cite
|
Sign up to set email alerts
|

Pesticide residues in fish from the Densu River Basin in Ghana

Abstract: The Densu River is a typical river flowing through agricultural areas in Southern Ghana. Six fish species from different locations in the river were sampled and analyzed for residues of pesticides and metabolites using GC with ECD/FID. The results of the study indicate that all the detected residues and metabolites in fish samples from the Densu River Basin were organochlorines (OCs). Among the pesticides residues analyzed, DDE, α-endosulfan, γ-HCH, δ-HCH, heptachlor and endosulfan sulphate, were predominant i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 13 publications
0
3
1
1
Order By: Relevance
“…This is true both for local studies by [9][10][11][12][13] as well as for studies from other regions carried out by [14][15][16][17]. However, OCP residues from Densu River [18] in Ghana were about 3 folds higher than the flood concentration from the current studies. Similarly, [19] and [20] recorded astronomical levels of pesticide residues in water samples from Lake Naivasha in Kenya and Benue River in Nigeria respectively (Table 5).…”
Section: Resultscontrasting
confidence: 40%
“…This is true both for local studies by [9][10][11][12][13] as well as for studies from other regions carried out by [14][15][16][17]. However, OCP residues from Densu River [18] in Ghana were about 3 folds higher than the flood concentration from the current studies. Similarly, [19] and [20] recorded astronomical levels of pesticide residues in water samples from Lake Naivasha in Kenya and Benue River in Nigeria respectively (Table 5).…”
Section: Resultscontrasting
confidence: 40%
“…The ratios of (p,p'-DDE + p,p'-DDD)/p,p'-DDT can be used to establish whether the contamination is due to recent input/application or historical/past use, because the levels of the parent compound (p,p'-DDT) in the environment decrease with time relative to its metabolites, p,p'-DDE and p,p'-DDD. A high ratio (> 1) indicates past use or old source of DDT which has been largely converted to DDE and DDD, while a low ratio (< 1) indicates recent use or exposure to the parent DDT or insignificant degradation (Jaga and Dharmani, 2003;Qiu et al, 2004;Fianko et al, 2013). The (p,p'-DDE + p,p'-DDD)/p,p'-DDT ratios were low (< 1) in most of the soil samples and in almost all sediments (Table 1 and Table 3) indicating recent use of DDT in nearby areas or old input of DDT without significant degradation.…”
Section: Discussion Profiles Of the Pesticide Residuesmentioning
confidence: 99%
“…For example, Fianko et al (2013) found high ratios of DDE/DDT in fish samples (with a mean of 2.51) indicating old input of DDT and significant degradation. Similarly, the study by Sosan et al (2015) found higher concentrations of p,p'-DDD and p,p'-DDE than the concentrations of p,p'-DDT in foodstuffs from markets in Ile-Ife, Nigeria indicating that the DDT had substantially metabolized into DDD and DDE.…”
Section: Discussion Profiles Of the Pesticide Residuesmentioning
confidence: 99%
“…Il est bien connu que les résidus de pesticides et métabolites peuvent être transportés des sources de contaminations vers les eaux souterraines et de surface à travers le ruissèlement des eaux, l'érosion des sols et causer des risques écologiques (Schulz, 2004 ;Shark et al, 2004 ;Hela et al, 2005 ;Boutron et al, 2011;Ouattara et al, 2012 ;Kalogridi et al, 2014 ). Cependant, les seules données disponibles sur la contamination des estuaires par les pesticides en Afrique se sont focalisées sur les organochlorés (Henry et Kishimba, 2003;EYA et al, 2006aEYA et al, , 2006bEssumang et al, 2009 ;Koffi et al, 2009 ;Fianko et al, 2013;Okoya et al, 2013 ;Kouakou et al, 2015) et les organophosphorés (Paré et al, 2013), bien que les autres familles de pesticides puissent causer des dangers pour la santé de l'homme et de l'environnement (Charlier et Plomteux, 2001 ;Blacker et al, 2010;Ardjouma et al, 2011 ).…”
Section: Introductionunclassified